Increasing Teacher Ability in Implementing Mind Map Based E-Modules by Strengthening Students' Independent Learning Character through IHT at Banjarharjo Kalibawang Kulon Progo Public Elementary School for Academic Year 2022/2023 - Kandibah, Umi (Universitas Islam Indonesia, 2024)
The aim of this research is to improve the ability of teachers to apply Mind Mapp-based E-Modules by strengthening students' independent learning character through IHT and improving the ability of researchers to manage IHT at the Banjarharjo Kalibawang Kulon Progo State Elementary School for the 2021/2022 academic year. The type of research carried out was School Action Research (PTS) which was carried out over 2 cycles consisting of 2 meetings. The subjects of this research were 8 teachers consisting of class teachers and subject teachers at the Banjarharjo Kalibawang Kulon Progo Public Elementary School. Observation results regarding the feasibility of implementing E-modules in each cycle, cycle I 1st meeting: reached 2.71: percentage 67.81%; following the 2nd meeting it reached 3.36; percentage 83.95%; following cycle II, 1st meeting, the average score reached 3.54; percentage 88.38%; following the second cycle II meeting the average score was 3.69; the percentage reached 92.19%. Based on participant activities, the average score for cycle I of the 1st meeting reached 3.06; percentage 76.42%; next cycle I, second meeting, the average score was 3.39; percentage 84.84%; Following are the results from cycle II of the 1st meeting, an average score of 3.54 was obtained; percentage 88.61%; Furthermore, the results obtained in the second cycle of the second meeting were an average score of 3.70; percentage 92.50%; Results of participants' assessments of researchers/resource persons for cycles I and II, the average score obtained for cycle I of the 1st meeting; 81.08%; following the 2nd meeting 84.30%, then in cycle II the 1st meeting reached 88.43%; Following are the results of the second cycle II meeting, the average score is 90.44%.